Implementasi Ekonomi Syariah Dalam Bingkai Ekonomi Pancasila - Jamaludin, Nur (Zhafir | Journal of Islamic Economics, Finance, and Banking, 2020)
The development of the sharia economy in Indonesia as the country with the largest Muslim population in the world is also inseparable from the development of the Islamic economy in the world, especially those from neighboring Malaysia. Starting in the 1993s marked by the establishment of the first Islamic bank, Bank Muamalat until now its growth continues to be encouraging. Economic and financial institutions as well as educational institutions that examine sharia values ​​as the basis have made a positive contribution to sharia economic growth. Regarding the growth of the Islamic economy in Indonesia, it is very interesting to study how its positioning or existence is in the Indonesian legal, political and economic system. This paper examines this relationship in order to get a conclusion of its compatibility with the economic system that we adhere to with a qualitative approach to literature study. The results of this study find that Islamic Economics and Pancasila Economics are both inseparable because they have high compatibility. Normatively, the objectives of the Pancasila Economy which are marked by Article 33 of the 1945 Constitution have the same principle in Islamic economics, namely the principles of gaining falah, socio-economic justice and equity and prosperity. The implication of this study is that Islam and Pancasila, especially in the economic field, cannot be separated.